Social and Macroeconomic Uncertainty and Private Savings: A Case Study of a Developing Economy - Siddiqui, Anjum; Waheed, Abdul; Mahmood, Haider (International Journal of Economics and Financial Issues, 2016)
We examine the effects of various new variables relating to uncertainty and find that “social uncertainty” in the form of increased crime is leading to portfolio substitution from bank accounts towards savings in durable goods and other real assets in a typical low middle income economy of Pakistan. Accounting for the cultural phenomena of savings in gold and non-bank real assets in South Asia, we have modeled macroeconomic uncertainty through both the levels and the volatilities of gold prices and the stock market index, as well as income volatility. We find that higher social and macroeconomic uncertainty leads to larger precautionary savings in non-bank assets and thereby results in lower residual savings in the National Income Accounts; this result is robust and invariant to various measures of uncertainty. We also find support for the Permanent Income Life Cycle hypothesis and “weak form” evidence for Ricardian equivalence. Keywords: Private savings, Uncertainty, Consumer Durables JEL Classification: D81, E21, E62